A Study and Analysis of Footfalls and Security using the Smart Alert System - G Nikhitha, B Jeevana Sai, C Murali Sree Krishna, M V Varshith, Dr. Brahmanada S.H (International Journal of Advanced Science and Technology, 2020)
The paper proposes the Smart monitoring system using a motion-triggered image capturing technology. The system can serve as a smart security surveillance module and at the same time, it can also be used for monitoring the footfalls at college libraries. In recent years we see cameras are fixed at all the corners of the building and a traditional CCTV camera can only record the live video. But this “SMART ALERT SYSTEM” having ESP32 CAM and PIR (passive infrared) sensor can detect even a slight movement immediately, captures the image of it, and sends it to the registered email ID.